Ethics and Learning Media from the Perspective of Hadith - Millah, Nurul; Qodir, Abdul; Hidayati, Noorazmah (Universitas Islam Negeri Raden Intan Lampung, 2026)
Learning in modern education tends to emphasize cognitive aspects and the use of technology, while the ethical and value dimensions are often neglected. This creates a gap between the effectiveness of learning and the formation of student character. This study aims to examine ethics and learning media from the perspective of the hadith and their relevance to contemporary education. The method used is qualitative research with a library approach, through an analysis of hadiths related to ethics and learning media, supported by Islamic education literature and modern educational theory. The results show that learning ethics in the hadith include obedience to Allah and the Messenger, an attitude of critical questioning, and respect for differences as the basis for character formation. Meanwhile, learning media from the hadith perspective is flexible and contextual, including the use of audio, visual, and audio-visual media that function to clarify understanding while internalizing values. The novelty of this study lies in the simultaneous integration of ethics and learning media from the hadith perspective and their reinterpretation in the context of digital education. Thus, this study offers an Islamic pedagogical model that is not only methodologically effective but also oriented towards values ​​and character formation.